Node.js Recipes - Gackenheimer, Cory (Apress Imprint: Apress, 2013)
Node.js Recipes is your one-stop reference for solving Node.js problems. Filled with useful recipes that follow a problem/solution format, you can look up recipes for many situations that you may come across in your day-to-day server-side development. Node.js is accessible to those who not only relish in server-side programming but also web developers who understand the ubiquitous language of the web. Node.js Recipes covers all the essential ingredients required to become a seasoned Node.js developer in no time - make it your indispensable reference today.